Como viver depois de Darwin?: limites e possibilidades das abordagens evolucionistas da moralidade - José Costa Júnior (2017)
The present work aims to develop a dialogue between philosophy and science from a critical analysis of the evolutionary investigations on morality. The main objective is to evaluate whether the various scientific investigations based on the evolutionary model structured by the british Charles Darwin produce illuminating expositions about elements such as (i) the human capacity to produce moral judgments, (ii) the content of our moral beliefs, and (iii) how we think about morality, among other. The development of the work is based on the presentation and critique of the different proposals that aim to understand morality and its elements starting from the evolutionist perspective. The first chapter presents the darwinian theory and some of its implications for human issues, along with Darwin's empirical hypothesis about the origins of the human moral sense. It also addresses the normative philosophy called social darwinism allegedly inspired by the developments proposed by Darwin. The second chapter deals with sociobiology, an investigation that seeks to understand the biological basis of animal behavior, and discusses the limits and possibilities of sociobiological explanations of human nature and morality. The third chapter addresses the evolutionary psychology scope, which aims to explain the psychological structure of the human species based on evolutionary understanding, together with empirical investigations of an evolutionary nature that study the possible natural origins of morality, with evidence from primatology, evolutionary anthropology, psychology, and neuroscience. The final conclusion of the thesis draws from the former chaptersconclusions and discusses whether the evolutionary understanding of the human animal and morality produces implications for moral philosophy, such as the need of its reevaluation derived from empirical investigations human nature. Finally, we show how new questions arise in the debate about relation between evolution and morality. In general, it is argued that, contrary to lowering or diminishing the status of humanity, the darwinian hypothesis can bring clarification about our condition. However, it is necessary to avoid the radicalisms and reductions proposed by some currents. Specifically, it is argued that a critical evolutionary understanding of the elements involved in human moral capacity may contribute to a more informed philosophical approach